ANALISIS PERBANDINGAN JUMLAH SIMPANAN BERDASARKAN SEGMENTASI DEMOGRAFIS PADA ANGGOTA KOPERASI WANGUN RAHARJA CIMAHI - Andri Irawan (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2016)
Cooperative is one of the company that bases its activities on the principle of people'seconomic movement based on the principle of kinship. Cooperatives are business organizationsowned and operated by the individual for the common interest.Type of research is a case study to compare the amount of deposits of Cooperativemembers Wangun Raharja based on demographic segmentation variable gender and number ofdeposits. This study is a continuation from previous research conducted by Irawan (2014). Statisticsused were non-parametric statistical analysis by using the Independent Sample Test. The populationin this study are members of the Cooperative Wangun Raharja while sampling method is done byusing judgment sampling is to take 100 members of the cooperative consisting of 50 members of themale and 50 female membersBased on the analysis by using the Independent Sample Test have shown variants and theaverage amount of deposits of male members and female Cooperative Wangun Raharja has thesame amount